Teachers’ effectiveness, cooperative learning, and servant leadership: examining the mediating role of satisfaction with studies in a Latin American university sample - Villar-Guevara, Miluska; García-Salirrosas, Elizabeth Emperatriz; Fernández-Mallma, Israel (Frontiers in Education, 2025)
IntroductionThe importance of addressing topics related to higher education is increasingly recognized, with greater impetus since the education sector has expanded rapidly worldwide since the second half of the 20th century. These educational conditions have created the need to evaluate the mediating role of satisfaction with studies in the influence of teachers’ effectiveness and cooperative learning on servant leadership in the context of higher education.MethodAn explanatory study was conducted with the participation of 2,165 university students from Latin America, with an almost equal distribution between women (51.8%) and men (48.2%), with ages ranging from 18 to 56 years (M = 21.26; SD = 3.48). Data were collected using an online self-report questionnaire employing the Student Evaluation of Teachers’ Effectiveness (SETE) scale, the Cooperative Learning Questionnaire (CLC), the Servant Leadership Short Scale (SLSS), and the Brief Scale of Study Satisfaction (BSSS).ResultsThe hypotheses were supported, observing the effect on satisfaction with studies of both teachers’ effectiveness (β = 0.185; p = 0.000; t = 6.297) and cooperative learning (β = 0.358; p = 0.000; t = 11.491); and the effect on servant leadership of both teachers’ effectiveness (β = 0.122; p = 0.000; t = 4.247), cooperative learning (β = 0.576; p = 0.000; t = 21.186), and satisfaction with studies (β = 0.151; p = 0.000; t = 7.734). Likewise, the results indicate the mediating role of satisfaction with studies in the effect of teachers’ effectiveness on servant leadership (β = 0.028; p = 0.000; t = 4.784), and of cooperative learning on servant leadership (β = 0.054; p = 0.000; t = 6.531).DiscussionThis new model suggests a re-evaluation of existing models on these topics. The results of this research provide valuable insights for higher education management and leadership seeking to achieve higher levels of academic satisfaction among Latin American university students. This model warrants special attention in future research, including the exploration of other potential factors and the application of these findings to diverse contexts and cultures.